EXAMINING PRE-SERVICE SCİENCE TEACHERS’ TECHNOLOGICAL PEDAGOGICAL DIFFERENT CONTEXTUAL KNOWLEDGE INVOLVING THE TOPIC OF RENEWABLE ENERGY SOURCES - Didem KARAKAYA CIRIT (Fırat University, 2019)
In this study utilizing the case study survey method, pre-service teachers’ Technological Pedagogical Different Contextual Knowledge (TPDCK) involving the topic of Renewable Energy Sources (RES) were investigated. RES-TPDCK designed according to transforming model was conceptualized as an integration of the subject matter, pedagogical, technological and different contextual knowledge in the study. Contextual knowledge is consist of five different categories; (1)Macro, (2)Mezo, (3)Sub-Mezo, (4)Micro ve (5)Sub-Micro context. 36 Pre-service Science Teachers, which were selected according to the techniques of nonprobability sampling, in their first, second, third and fourth grade in the Department of Science Education Program during 2014-2015 academic year participated in the study. Different contexts based semi-structured individual interviews for the PSTs’ TPDCK was used as data collection tools in this study. The content analysis method was used for the data analysis. Findings obtained from the data analysis showed that pre-service teachers’ TPDCK levels were approximately same and their RES-TPDCK was inadequate. It was also found that they had partial understandings on sub-mezo, micro and sub-micro contexts, while the most of them neglected the macro and mezo contexts in the teaching process of pre-service teachers. It was understood that pre-service science teachers had non-scientific views about the knowledge of technology-supported assessment, ignoring contextual factors in the teaching process of RES. The conclusions of this study were discussed on teacher training system.